Polish Roads Toward the Regionalization of Railway Passenger Transport - Juliusz Engelhardt (Przegląd Komunikacyjny)
Abstract: The paper is devoted to the functioning of passenger rail transport in Polish regions. In the first part, the content of the paper is a retrospective look at the beginnings of the policy of regionalization of regional rail transport, which, according to the first government declarations, date back to 1995. However, the actual beginning of decentralization reforms in the Polish railway industry was provided by the provisions of the Act of 2000, on the basis of which a quasi-holding of companies was established. railways under the contractual name of the PKP Group, and the obligation to organize and finance regional railway transport was imposed on the Provincial Governments. Because this first attempt at reform had serious shortcomings, shortly after its implementation there was a deep crisis in regional rail transport, lasting with varying intensity until 2008. The government reform implemented at the end of 2008, despite numerous difficulties, stabilized the situation in the field of regional rail transport. and new local government companies have appeared in this sector. The long-term effects of this reform are positive both in the scale of the entire railway system in Poland and in individual regions - local government railway companies currently serve a significant part of the market. In the final part of the considerations, attention was focused on the possible directions of structural and ownership changes in the following years in relation to local government companies and the POLREGIO company and on the possible positive effects of the full implementation of the EU's fourth railway package.